Monitoring Parking Space Availability via Zigbee Technology - Hee, Chien Yee; Yusnita, Rahayu (IJFCC, 2014)
With the rapid growth of vehicle availability and usage on the road in recent years, finding a vacant car parking space is becoming more and more difficult which resulting in a number of conflicts such as traffic problems. In this paper, a prototype of Monitoring Parking Space Vacancy System is introduced using wireless technologies to alleviate the traffic problems. The system includes two modules, parking lot vacancy monitoring module, and master module. Parking lot vacancy monitoring module consists of digital infrared sensor, liquid crystal display (LCD), and Zigbee module which are interfaced with PIC microcontroller. Master modules include laptop GUI display, and Zigbee modules. The user can get the status of parking lot vacancy through the LCD of monitoring parking vacancy module. The Zigbee transceiver on monitoring parking vacancy module which interfaced with microcontroller is to transmit the infrared sensor data when the digital infrared sensor detects the presence of vehicle in the parking areas and thus provide the status of the parking lot to be displayed in master module with Graphical User interface (GUI).